2021
DOI: 10.3389/fnins.2020.570848
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cerebral Venous Oxygen Level and Cognitive Status in Patients With Alzheimer’s Disease Using Quantitative Susceptibility Mapping

Abstract: PurposeTo quantitatively assess the blood oxygen levels of the cerebral vein using quantitative susceptibility mapping (QSM), and to analyze the correlation between magnetic susceptibility value (MSV) and clinical laboratory indicators/cognitive scores in patients with Alzheimer’s disease (AD).Materials and MethodsFifty-nine patients (21 males and 38 females) with clinically confirmed AD (AD group) and 22 control subjects (12 males, 10 females; CON group) were recruited. Clinical data and laboratory examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This result agrees with the higher OEF found by Chiang et al in cognitively impaired subjects ( Chiang et al, 2022 ). However, between-group differences in the average were only moderately significant in veins located in the thalamus and dentate nucleus ( Liu et al, 2020 ). This study also found significant correlations between the average venous and clinical scores assessing cognitive status (i.e., the Mini-mental State Examination, Montréal Cognitive Assessment and Clock Drawing Task, and Activity of Daily Living Scale), demonstrating a relationship between the average venous and clinical cognitive assessment.…”
Section: Applications To Aging and Neurodegenerationmentioning
confidence: 98%
See 1 more Smart Citation
“…This result agrees with the higher OEF found by Chiang et al in cognitively impaired subjects ( Chiang et al, 2022 ). However, between-group differences in the average were only moderately significant in veins located in the thalamus and dentate nucleus ( Liu et al, 2020 ). This study also found significant correlations between the average venous and clinical scores assessing cognitive status (i.e., the Mini-mental State Examination, Montréal Cognitive Assessment and Clock Drawing Task, and Activity of Daily Living Scale), demonstrating a relationship between the average venous and clinical cognitive assessment.…”
Section: Applications To Aging and Neurodegenerationmentioning
confidence: 98%
“…One study on Alzheimer’s disease ( Liu et al, 2020 ) has used QSM to measure the average in various cerebral veins of patients relative to elderly healthy controls, based on the hypothesis that cerebral blood flow impairment in Alzheimer’s disease may be associated with cognitive decline. The average venous was generally higher in patients than in controls, corresponding to lower venous oxygen levels.…”
Section: Applications To Aging and Neurodegenerationmentioning
confidence: 99%
“…A different approach has been performed using high-field MRI in evaluating deep medullary veins tortuosity as a marker for SVD [119]. This application, as the evaluation of collagenosis of the deep medullary veins [11,94,97] and the measurement of venous oxygen levels [120], is outside the aims of this review, and they will not be specifically addressed. Moreover, superficial cortical veins (SCVs) were evaluated using MRI in a study on 344 healthy volunteers aiming to establish a relation between cognition and the diameter, length, or tortuosity index of the SCVs in the bilateral cerebral hemispheres without success [121].…”
Section: Potential Contribution Of the Venular Involvement To Neuroim...mentioning
confidence: 99%
“…As such, imagingbased, noninvasive measurements of the parameters have been of great interest to clinics. In particular, recent MRI-based methods, 2,3 which aim to be a nonradiative, cost-efficient alternative to gold standard PET-based measurements using 15 O-labeled radioactive tracers, have shown promise that regional OEF may serve as a potential biomarker in a number of brain diseases, including ischemic stroke, 4 multiple sclerosis, 5 Alzheimer's disease, 6 and cognitive impairment. 7 Two representative MRI techniques among the few that enable OEF mapping are calibrated BOLD (cBOLD) 8 and quantitative BOLD (qBOLD).…”
Section: Introductionmentioning
confidence: 99%